On the triple helix model for promotion of innovations in Vietnam - Dung, Bui Tien (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Innovations in Vietnam need suitable models for a better impact to the socio-economic development of the country. The triple helix to link the Public sector, businessmen and researchers get attention of various local and international study teams. In Vietnam, from macro vision, among 150 thousand of producing enterprises, only 0.1 - 0.3% of turnovers is invested for technological innovation and the actors of the triple helix remain relatively separated which leads to difficulties in creation of high added value. Based on experiences of many countries, this research deals with the triple helix models which can be applied effectively in Vietnam. Code: 13030701